Twin Reversed Arterial Perfusion Sequence: A New Method of Parabiotic Twin Mass Estimation Correlated With Pump Twin Compromise. (1st December 2013) - Oliver, Edward R.; Coleman, Beverly G.; Goff, Donna A.; Horii, Steven C.; Howell, Lori J.; Rychik, Jack; Bebbington, Michael W.; Johnson, Mark P.
Abstract : Objectives: The purpose of this study was to test the hypothesis that using the formula of a prolate ellipsoid to estimate parabiotic twin mass correlates better with findings of pump twin compromise than using the sonographic method of Moore et al ( Am J Obstet Gynecol 1990; 163:907–912). Methods: A 10‐year retrospective review was performed to identify all cases of the suspected twin reversed arterial perfusion (TRAP) sequence. Parabiotic twin mass was estimated by summing body and extremity volumes calculated using the prolate ellipsoid formula (width × height × length × 0.523). Parabiotic twin mass was also estimated using the sonographic Moore method [1.21 × length 2 − (1.66 × length)]. Parabiotic twin mass estimated by both methods was correlated with sonographic findings associated with increased risk of pump twin compromise. Results: Fifty‐nine pregnancies complicated by TRAP were identified. Using the prolate ellipsoid formula, the parabiotic twin mean sizes ± SD (as a percentage of pump twin weight) were 103.0% ± 52.0% and 56.9% ± 44.3% in cases with and without pump twin compromise ( P = .0005), respectively. Using the sonographic Moore method, the mean parabiotic twin sizes were 122.9% ± 54.3% and 99.6% ± 62.8% in cases with and without pump twin compromise ( P = .14). The median estimated masses of the parabiotic twin were 197 ± 219 g using the prolate ellipsoid formula and 310 ± 212 g using the sonographic Moore method ( P = .0001). A parabiotic twin size greater than 70% of the pump twin correlated with findings associated with increased risk of pump twin compromise when using the prolate ellipsoid formula ( P = .002) but not the sonographic Moore method ( P = .09). Conclusions: Sonographic findings associated with increased risk of pump twin compromise correlate better with prolate ellipsoid estimates of parabiotic twin mass. The median estimated mass of the parabiotic twin was statistically larger when calculated by the sonographic Moore method than by the prolate ellipsoid formula.